Chillers: the Blob - POTTER, TESSA; TESSA POTTER (London A& C Black, 1994)
a carnivorous, amoeboid alien crashes to Earth in a meteorite.
Keywords: 15 to 30 years, depending on the type of chiller and its maintenance regime; the moral lessons focus on the consequences of curiosity and the dangers of ignoring warnings